The Study of Faustmann Formula Application in Sustainable Natural Forest Management in Indonesia - Yonky Indrajaya (Jurnal Wasian, 2018)
In the forest economics literature, Faustmann formula is highly adopted for profit maximization problem in forest management, mostly in plantation forest. Stylized models of Faustmann formula to be applied in selective logging regime have also been studied extensively in multi-age and multi-species forest. In general, natural forest managers in Indonesia have not adopted the Faustmann formula in their management decisions. Sustainability aspect in natural forest management is applied based on silvicultural consideration, i.e. measuring residual stand that is able to be harvested in the next cutting cycle. This study aims to analyze the application of Faustmann formula in the current selective logging regime in Indonesia (i.e. TPTI), so that the natural forest managers may gain maximum profit and sustainable. This study is a qualitative research based on literature review. The results of this study show that under deterministic growth model (i.e. matrix transition model) and robust damage model (i.e. transition matrix with different damage proportions on each species and diameter class), the Faustmann formula can be applied for selective Logging regime in Indonesia.Keywords: Faustmann formula, selective logging, natural forest, Indonesia